Young men who have sex with men's use of social and sexual media and sex-risk associations: cross-sectional, online survey across four countries. (20th January 2016) - Lorimer, Karen; Flowers, Paul; Davis, Mark; Frankis, Jamie
Abstract : Objective: There has been an increase in new HIV diagnoses among young men who have sex with men (YMSM) over the past decade in both UK and US contexts, with online sex-seeking implicated in driving this development. This study sought to examine YMSM's use of a variety of social and sexual networking websites and 'apps', and assess sexual risk behaviours. Design: YMSM were recruited from across four countries in Britain and Ireland, via an online survey using convenience sampling. Data were collected from 2668 men, of whom 702 were aged 18–25 years. Results: Facebook use was almost ubiquitous and for largely social reasons; sexual media use was common with 52% using gay sexual networking (GSN) websites frequently and 44% using similar apps frequently. We found increased odds of high-risk condomless anal intercourse associated with the length of time users had been using GSN websites and lower levels of education. We found no significant differences across the four countries in sexual risk behaviours. Conclusions: YMSM are a heterogeneous population with varied sexual health needs. For young men with digital literacy, individual-level online interventions, targeted and tailored, could be directed towards frequent users with lower levels of education. Variation in demographic characteristics of GSN websites and app users may affect who interventions are likely to reach, depending on where they are targeted. However, interventions, which may catch young men earlier, also provide a major opportunity for reducing sexual health inequalities.